Gamificação na educação: uma proposta para a aplicação da cultura digital prevista na BNCC - (:unkn) unknown (Brasil, 2019)
The new National Curricular Common Base - BNCC of Early Childhood Education and Basic Education, presents significant changes for Basic Education, changes that must be implemented by 2020, the novelty of the document are the skills that permeate all the curricular components among which highlights the Competence 5 that has the Digital Culture. Since technology must permeate the entire curriculum, Gamificación is an active methodology that uses game tools in non-games and presents itself as a great proposal in education to promote teaching and learning in the 21st century using technologies and tools to achieve the goals set by Digital Culture.
Keywords: Gramificação - educação; Metodologias ativas - educação; Cultura digital - BNCC; CNPQ::CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM